2022
DOI: 10.1111/opo.13031
|View full text |Cite
|
Sign up to set email alerts
|

Myopia control with dual‐focus soft contact lenses during the first year of measures to contain the COVID‐19 pandemic

Abstract: This study compared refractive and axial length (AL) changes in children wearing dual-focus soft contact lenses for myopia control (MiSight®) with myopic children wearing spectacles one year from the start of lockdown during the COVID-19 pandemic. Methods: This retrospective, descriptive, parallel-group, observational study reviewed the charts of 11 children who began treatment for myopia control with dual-focus soft contact lenses for myopia control (MiSight®) in March 2020 and 11 matched spectacle-wearing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Consistent with this finding, Huang et al suggested that the addition of multifocal SCLs designed for inducing myopic defocus did not follow a “the higher, the better” principle, and that a defocus of + 6.00 D was ineffective for controlling myopia progression [ 54 ]. The effectiveness of DISC lenses in the present study and MiSight® lenses in other studies [ 17 , 18 , 25 ] indicates that bifocal SCLs with adds of + 2.00 D to + 2.50 D may achieve adequate myopic defocus. Moreover, the treatment zone size and the pupil diameter were also important factors influencing the myopia controlling effects of bifocal SCLs [ 23 ].…”
Section: Discussionsupporting
confidence: 64%
“…Consistent with this finding, Huang et al suggested that the addition of multifocal SCLs designed for inducing myopic defocus did not follow a “the higher, the better” principle, and that a defocus of + 6.00 D was ineffective for controlling myopia progression [ 54 ]. The effectiveness of DISC lenses in the present study and MiSight® lenses in other studies [ 17 , 18 , 25 ] indicates that bifocal SCLs with adds of + 2.00 D to + 2.50 D may achieve adequate myopic defocus. Moreover, the treatment zone size and the pupil diameter were also important factors influencing the myopia controlling effects of bifocal SCLs [ 23 ].…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies on myopia control therapy commonly selected SER and AL as primary outcomes, and SER was chosen as the primary endpoint [33][34][35]. However, the change of AL was more sensitive to the short-term pro- gression of myopia in children, according to our clinical research.…”
Section: Results Of Endpointsmentioning
confidence: 89%
“…In these last years, the increased time in near work with digital devices [ 41 , 42 ] together with the reduced time spent outdoors due to the COVID-19 pandemic may have increased the risk of myopia onset and progression in children [ 43 , 44 ], a side effect of the measures to contain the pandemic that will only become apparent in the next few years [ 45 , 46 ]. Interestingly, recent works have proposed that time spent outdoors may have also had a role in the efficacy of dual-focus soft contact lenses for myopia control [ 47 ] and atropine [ 48 , 49 ] during the pandemic, while another recent study has proposed that dual-focus soft contact lenses for myopia control are effective regardless of time spent outdoors [ 50 ]. Another recent work has proposed a stronger association between digital screen use and myopia progression than between myopia and time spent outdoors during the strict lockdown [ 45 ].…”
Section: Discussionmentioning
confidence: 99%